2019
DOI: 10.1016/j.jad.2018.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal depression among a global sample of Spanish-speaking women: A sequential-process latent growth-curve analysis

Abstract: Given these findings, it is imperative that providers pay attention to, and assess for, depressive symptoms and identified buffers for depression, especially when working with women from diverse communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 50 publications
1
8
2
1
Order By: Relevance
“…The results showed that the level of anxiety and depression increases from the beginning of pregnancy to the second trimester of pregnancy and has an inverse relation with the level of education. The relationship between education level and psychological health has already been reported; however, the increase in the level of depression and its relative frequency in the present study is in contrast with the results of other research carried out on the general population and indicated a slowdown in depression during pregnancy [20,22].Hu et al also reported that the frequency of depression decreases during the three trimesters of pregnancy [23]. Comparing the prevalence of depression in her study in the first trimester of pregnancy (14.0%), with the present study suggests that women with low-risk pregnancy start pregnancy with less depression, but with the advancement of pregnancy, the level of depression increases.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The results showed that the level of anxiety and depression increases from the beginning of pregnancy to the second trimester of pregnancy and has an inverse relation with the level of education. The relationship between education level and psychological health has already been reported; however, the increase in the level of depression and its relative frequency in the present study is in contrast with the results of other research carried out on the general population and indicated a slowdown in depression during pregnancy [20,22].Hu et al also reported that the frequency of depression decreases during the three trimesters of pregnancy [23]. Comparing the prevalence of depression in her study in the first trimester of pregnancy (14.0%), with the present study suggests that women with low-risk pregnancy start pregnancy with less depression, but with the advancement of pregnancy, the level of depression increases.…”
Section: Discussioncontrasting
confidence: 99%
“…But widespread and comprehensive changes during pregnancy may have a different effect on the psychological health of women during different stages of the prenatal period and it needs to be aware of changes in psychological health during different periods of pregnancy. However, in previous studies, the psychological conditions of pregnant women evaluated during pregnancy; but, there is limited information on the changes in psychological status during low-risk pregnancies [20]. Therefore, the present study was conducted by designing prospective study with the aim of evaluating the changes in psychological symptoms of women with weeks of gestational age.…”
Section: Introductionmentioning
confidence: 99%
“…A major strength of this study is that it is one of the first to look at longitudinal depression trajectories among pregnant and postpartum women in sub-Saharan Africa. Thus, this study helps to address a large gap in the perinatal depression trajectory literature, which tends to focus on high income, well-resourced countries, with some exceptions (Carter, Bond, Wickham, & Barrera, 2018). Another strength of this study is the large sample size (N=831).…”
Section: Discussionmentioning
confidence: 99%
“…We believe this is in large part due to the fact that four of the five senior members of i4Health identify as Latinx (Alinne Barrera, Eduardo Bunge, Ricardo Muñoz, and Blanca Pineda). We have worked on studies about perinatal depression on Spanish-speaking women (Barrera and Nichols, 2015; Carter et al, 2019) and online prevention of postpartum depression (Barrera et al, 2015). We have also worked on studies to reach Spanish-speaking smokers (Muñoz et al, 2006, Muñoz et al, 2009, Muñoz et al, 2014), and how to increase recruitment of Spanish- and English-speaking participants (Barrera et al, 2014; Bunge et al, 2019).…”
Section: Difficulties Including Diverse Populations In Health Studiesmentioning
confidence: 99%